Three-Dimensional Morphometric Analysis of Penetrative Depth and Size of Nonarthritic and Degenerative Arthritic Glenoids: Implications for Glenoid Replacement in Shoulder Arthroplasty - Jung, Hong Jun (Clin Orthop Surg, 2020)
BACKGROUND: Shoulder arthroplasty is technically demanding and relies heavily on the precision of surgical techniques. Proper glenoid component sizing plays a crucial role in successful shoulder arthroplasty. We measured the size and penetrative depth of the glenoid for peg or screw fixation in nonarthritic and degenerative arthritic shoulders by using three-dimensional computed tomography to determine the reference dimensions of the glenoid in nonarthritic and degenerative arthritic shoulders. METHODS: From January 2010 to January 2011, data on two groups of patients were collected and reviewed. Group 1 comprised 38 patients who underwent surgical treatment due to fracture of the proximal humerus and who had no evidence of a pathological glenoid. Group 2 comprised 14 patients who underwent surgical treatment due to osteoarthritis of the glenohumeral joint. The height (maximal superoinferior diameter) of the glenoid was measured, and the width (anteroposterior [AP] diameter) of the glenoid was measured at five different levels (H1–H5). Axial images were taken at H1–H5 levels, the AP glenoid diameter of each was divided into eight areas, and division points were labeled as W1–W7. The penetrative depths between the near cortex and far cortex of the glenoid (thickness) at each point (W1–W7) were measured. RESULTS: The overall mean glenoid height was 37.67 ± 4.09 mm in nonarthritic glenoids and 39.42 ± 3.54 mm in degenerative arthritic glenoids. The nonarthritic glenoid was significantly thicker than the degenerative arthritic glenoid at the H1W3, H1W4, H1W5, H2W7, H3W1, H3W6, H3W7, H4W5, H4W6, H4W7, H5W4, H5W5, H5W6, and H5W7 points. The posteroinferior quadrant had the smallest penetrative depth in both nonarthritic and degenerative arthritic glenoids. Also, the degenerative arthritic glenoids were significantly thinner than the nonarthritic glenoids along the posterior and inferior parts of the glenoid. CONCLUSIONS: The posterior and inferior parts of the degenerative arthritic glenoid appears thinner than the nonarthritic glenoid. Thus, caution has to be taken when drilling the screw hole or inserting screws into the posteroinferior parts, where the glenoid is thinner than 15 mm on average, to avoid penetration of the far cortex.